Does Local Wisdom Offer Adequate Protection for MSMEs? - Fatahillah Fatahillah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This research explores how local wisdom integrates with formal legal frameworks to offer legal protection for MSMEs in Lhokseumawe, Indonesia. Traditionally, MSME operations in the region have been guided by informal agreements and trust-based relationships, which, while effective in local settings, do not sufficiently address the legal and financial complexities encountered in broader markets. By incorporating formal legal structures alongside Islamic financial principles, such as musharakah (partnership) and mudharabah (profit-sharing), MSMEs benefit from both ethical and legal protection. This hybrid approach allows MSMEs to secure contract enforcement and resolve disputes, while remaining aligned with cultural and legal norms, enabling successful operations in both local and global markets. The study emphasizes the need for educational programs to raise awareness among MSME owners about the benefits of formal legal protections and Islamic financial instruments. These educational efforts are crucial for improving transparency, promoting risk-sharing, and facilitating interest-free financing options for MSMEs. By integrating local wisdom with formal legal frameworks, MSMEs can strengthen their resilience and competitiveness, especially in sectors like manufacturing and construction, where formal contracts play a vital role in protecting business interests. The research concludes with recommendations for further enhancing MSME legal protection through a more cohesive integration of local wisdom and formal legal mechanisms. This integrated approach will help MSMEs improve their competitiveness, access broader opportunities, and ensure long-term sustainability in an increasingly complex economic environment.